Pelatihan Terdepan Siswa SMK dalam Menghadapi Revolusi Industri 4.0 di SMK Master Indonesia Bogor - Rizky, Yulizan; Alfikri, M Reza; Firdaus, Imam Maulana (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The high rate of unemployment among SMK graduates in Indonesia, which has been recorded as one of the highest, is a serious challenge that needs to be addressed immediately. Bogor, as an industrial area that should have great potential to absorb labor, faces a similar dilemma. To overcome this problem, this program was conceived with the main objective of educating SMK students on skills that are crucial in facing the dynamics of the Industrial Revolution 4.0. The approach adopted through interactive discussions allows participants to be actively involved in understanding key concepts. Students' knowledge and understanding was then assessed through a pre-test and post-test scheme detailing the progression of their understanding before and after the program. The results show that overall, students have managed to grasp a more in-depth picture of the skills that are absolutely necessary in the face of the Industrial Revolution 4.0 era, providing a strong foundation to solve the problem of unemployment of SMK graduates in the future.